2023
DOI: 10.1071/fp23036
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles protect tillering in drought-stressed wheat by improving leaf water relations and physiological functioning

Muhammad Sarwar,
Muhammad Farrukh Saleem,
Najeeb Ullah
et al.

Abstract: The tillering phase of wheat (Triticum aestivum) crops is extremely susceptible to drought. We explored the potential of silver nanoparticles (AgNPs) in protecting wheat genotypes from drought injury during this sensitive stage. After treating with AgNPs (60 ppm), the plants were submitted to different water levels; i.e. 100% field capacity (FC), 75% FC (mild drought), 50% FC (moderate drought) and 25% FC (severe drought) from 15 to 41 days after sowing (tillering phase). Leaf physiological data were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Tran et al (2023) found that compared with control, seeds treated with MSNs (Mesoporous silica nanoparticles) showed higher seed germination and greater primary root length in Arabidopsis. Another study by Sarwar et al (2023) showed that silver nanoparticles (60 ppm) can protect tillering in drought-stressed wheat by improving leaf water relations and physiological functioning, showing significantly restored leaf physiological functioning and increased grains per plant (up to 22%).…”
Section: Nanobiotechnology Approach To Improve Plant Drought Tolerancementioning
confidence: 99%
“…Tran et al (2023) found that compared with control, seeds treated with MSNs (Mesoporous silica nanoparticles) showed higher seed germination and greater primary root length in Arabidopsis. Another study by Sarwar et al (2023) showed that silver nanoparticles (60 ppm) can protect tillering in drought-stressed wheat by improving leaf water relations and physiological functioning, showing significantly restored leaf physiological functioning and increased grains per plant (up to 22%).…”
Section: Nanobiotechnology Approach To Improve Plant Drought Tolerancementioning
confidence: 99%
“…Researchers have reported that NP application contributes to the regulation of antioxidant enzyme activity and cellular water balance [31]. Also, some researchers stated that AgNPs have the potential to develop resistance against drought stress in different plants such as wheat [42,43], eggplant [44], thymus [45], lettuce [46] and lentil [47].…”
Section: Introductionmentioning
confidence: 99%
“…When previous reports on drought are examined, it is thought that NP applications can be an effective alternative to alleviate the negative effects of drought. As a matter of fact, different NP applications have shown positive results in reducing the effects of drought in various plants [31,32,[42][43][44]46,47], but no research reporting the effects of AgNPs on boysenberry has been found. Research to reduce yield loss due to drought is important for the future of this plant, which has important benefits for human health and high economic value.…”
Section: Introductionmentioning
confidence: 99%